(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Febrile seizures are the most common type of seizures in infancy, affecting 2–5% of children under five years of age. Understanding the risk factors associated with febrile seizures is vital for early diagnosis, prevention, and management. To identify and assess the risk factors related to febrile seizures among children admitted to Mosul Pediatric Teaching Hospitals. A descriptive cross-sectional study was conducted on 100 children aged between 6 months and 5 years who presented with febrile seizures at Mosul Pediatric Teaching Hospitals from January to December 2024. Data were collected through structured caregiver interviews and hospital records. Variables included age, gender, family history of febrile seizures or epilepsy, degree and duration of fever, birth history, and immunization status. Most cases (62%) were males. Most children (78%) were aged between 12 and 36 months. A positive family history of febrile seizures was found in 46% of cases, and 35% had a history of neonatal complications. The mean peak temperature recorded was 39.5°C. Simple febrile seizures were more common (74%) than complex ones. A statistically significant association was observed between family history and recurrence of febrile seizures (p<0.05). Conclusions: Febrile seizures are more prevalent in males and in children aged 1–3 years. Family history, higher fever, and neonatal complications are significant risk factors. Awareness and early intervention can reduce anxiety and recurrence.